Application of PIV measurement techniques to study the characteristics of flame–acoustic wave interactions. (October 2015) - Chen, Li-Wei
Abstract: The present paper introduce the development of the experimental setup and measurement methodologies to study the structure of acoustic wave and the interaction between the acoustic fields and flame flow inside a square tube by using a time-resolved Particle Image Velocimetry (PIV). The design of signal synchronisation system, the selection of seeding particles, the test of seeding methods and the statistical analysis of the PIV data were introduced. The titanium dioxide (TiO2 ) was selected as the seeding particle for the PIV. The accuracy of synchronisation system was checked by a simple experiment. A time-resolved PIV results showed that the acoustic velocity difference was less than 2.8% at specific phase angle over 1000 excitation cycles at an excitation frequency of 385 Hz. For the case of hot flame gas, the largest difference is 4.4% over 100 excitation cycles at an excitation frequency of 10 Hz. Results proves that the present experimental system has high reliability to measure and analyse the characteristics of flame–acoustic interactions. Highlights: The experimental system was developed to observe the flame/acoustic wave. Time-resolved PIV system and synchronisation system were built. The accuracy of synchronisation system was less than 2.8% difference at specific phase angle over 1000 excitation cycles. The experimental system is proved that suitable for the study of flame–acoustic wave interactions.